Carboxytherapy for striae distensae: A promising modality. (3rd December 2020) - El‐Domyati, Moetaz; Hosam El‐Din, Wael; Medhat, Walid; Ibrahim, Michel R.; khaled, Yasmin
Abstract: Background: Striae distensae (SD) is a very common skin problem. Although a lot of treatment modalities have been proposed, few of them are effective. Recently, carbon dioxide therapy (CDT) or carboxytherapy was used in many indications of cosmetic dermatology such as SD. Objectives: To objectively evaluate the use and effectiveness of CDT for treatment of SD. Patients and methods: Twenty patients were subjected to 8 sessions of CDT injection at 2‐week intervals using carboxy‐gun. Patients were photographed, and skin specimens were obtained from the treated area before and after 4 months of treatment. Using a computerized 3D camera, skin topography was objectively analyzed before and after treatment. Evaluation of collagen and elastic fibers by special histopathological staining, in addition to histometric analysis, was also done to evaluate treatment efficacy. Results: Clinically, SD was statistically significantly improved after CDT injection compared with baseline (mean percentage of improvement of length and width, 59.8 ± 15.9; P < .05). Meanwhile, the improvement observed by the 3D camera correlated with the clinical improvement. Histometric analysis showed an increase in epidermal thickness ( P < .0001) in association with re‐appearance of rete ridges following treatment. Histochemical evaluation of changes in elastic and collagen fibers after treatment showed better organization of curled and fragmented elastic fibers, which was accompanied by an increase in collagen content that became denser, arranged in bundles and parallel to the epidermis. Conclusions: CDT is an effective, promising, and simple minimally invasive procedure for improving SD with few side effects and low downtime.